Synergistic Effect of Adjustments of Elastic Stockings to Maintain Reduction in Leg Volume after Mechanical Lymph Drainage - José Maria Pereira de Godoy; Renata Lopes Pinto; Ana Carolina Pereira de Godoy; Maria de Fátima Guerreiro Godoy (International Journal of Vascular Medicine)
The objective of the present study was to evaluate the effect of elastic compression stockings on volumetric variations of lymphedematous limbs between mechanical lymph drainage sessions. Eleven patients with Grade II leg lymphedema, regardless of etiology, were evaluated in a randomized clinical trial. The ages ranged from 47 to 83 years old with a mean of 62.4 years. Participants were submitted to mechanical lymph drainage (RAGodoy) associated with adjusted and unadjusted knee-high elastic compression stockings (20/30 Venosan). The effect of these stockings on the maintenance of volumetric reductions between sessions of lymph drainage was assessed. In all, 33 evaluations were carried out, 18 of patients using well-adjusted stockings and 15 with badly-adjusted stockings. The differences in volumes were significant (unpaired t-test; P-value < 0.0001). Adjusting the compression provided by elastic stockings according to the size of the leg has a synergistic effect in reducing volume during mechanical lymph drainage.